TOURISM AS A WAY TO EXPAND THE HUMAN LIFE SPACE - L. V. Martseniuk; T. Yu. Charkina (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose of the work is to substantiate the development of railway tourism in the context of human needs in accordance with the theory of individual life space. Methodology. Theoretical and methodological basis of the study is the provisions of the economic theory, management theory, corporate governance. The rational activity of travel agencies is based on the principles of economic equilibrium; Ukrainian population demand for railway tourism was determined with the help of market research and anonymous survey; to explore the real balance between the demand for tourist rail transport and the potential of the required volume of services the paper suggests the balance method. Since any travel company is an open system and is completely dependent on environmental factors, we proposed a method for estimating the factors of internal and external environment. Originality. The element of originality is compilation of existing concepts to the definition of the individual as a subject of life property, for the understanding of human relationships and its external environment. The paper developed the issue of the ability to influence the value of human life space with the help of tourist services. Conclusions. Market research conducted by the author has shown that in Ukraine there is a certain demand for tourist transport by rail, because it is more reliable, safer and more comfortable than the road transport. It is proved that the development of a new innovative project is very timely, as it will allow: to develop tourist infrastructure of Ukraine and bring it to the domestic and foreign tourists; replenish the state and local budgets by tourists; create new jobs for the population and improve their living level; partially reduce the loss-making passenger sector by increasing the volume of rail transport; expand life space for the people of Ukraine that will allow raising the intellectual level of the individual.